Integrating oral health into primary healthcare: lessons from project OHE-NCHeW (oral health education for nurses and community health workers) in Nigeria - Oladayo, Abimbola M.; Lawal, Folake B.; Sofola, Oyinkansola O.; Uti, Omolara G.; Oyapero, Afolabi; Aborisade, Adetayo; Olujitan, Mojisola; Fagbule, Omotayo F.; Williams, Adeola T.; Dedeke, Aderonke; Idiga, Ejiro; Abdul-Kabir Adegoke, Yahya-Imam; et al. (Frontiers in Oral Health, 2025)
IntroductionOral health disparities in Nigeria highlight the need to integrate basic oral health into Primary Health Care (PHC). Project OHE-NCHeW (Oral Health Education for Nurses and Community Health Workers) was developed to train PHC workers in providing basic oral health care, education, and referrals in underserved communities. This study explored the impact of the training program on participants' knowledge, referral practices, and patient outcomes, and gathered feedback to optimize the program for future implementation.MethodsUsing a qualitative phenomenological approach, five focus group discussions (FGDs) were conducted with participants to gather insights on knowledge acquisition, changes in referral practices, and barriers or facilitators to implementation. Audio recordings were transcribed verbatim and analyzed thematically using the CREATIVE framework. Additional feedback from trainers and observed patient impact were also considered.ResultsThe trained PHC workers reported enhanced knowledge and confidence, resulting in improved patient education and referrals. Patients also noted better oral health literacy and increased trust in dental referrals. Facilitators viewed the program as valuable and feasible, emphasizing the importance of ongoing training, resource allocation, and policy integration to maintain the program's impact. Key barriers included insufficient resources, lack of supervision, and cultural beliefs.DiscussionThe pilot training enhanced PHC worker capacity and was positively perceived by trainers. Patients reportedly responded favorably, indicating potential impact. However, addressing identified systemic and resource barriers is crucial for sustainable integration. This study offers multi-perspective insights for optimizing oral health integration within PHC in similar settings.